Malvinas and its School Transmission, a Field of Tensions in the Far South (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
This article proposes an analysis of the policies of curricular reform for recent Argentine history, since the passage of the National Education Law in 2006; focusing on the problems related to the inclusion of the topic Malvinas, as a content of obligatory education for secondary school. From a local history approach, it addresses the construction of the senses and specific meanings that it acquires in the society of Tierra del Fuego. The theoretical-methodological instruments of the critical theory of the curriculum and its articulation with the procedures of oral history, allowed us to analise the curricular texts and the testimonies produced in the interview situation. This includes sources generated with different key actors –teachers, ministerial referents and war veterans–. The meanings related to the war allow us to give an account of the social experiences of recent fuegian history.
Keywords: Teaching, Recent past, Malvinas, Tierra del Fuego